2017
DOI: 10.1089/bfm.2017.29038.ajk
|View full text |Cite
|
Sign up to set email alerts
|

ABM Clinical Protocol #3: Supplementary Feedings in the Healthy Term Breastfed Neonate, Revised 2017

Abstract: A central goal of The Academy of Breastfeeding Medicine is the development of clinical protocols for managing common medical problems that may impact breastfeeding success. These protocols serve only as guidelines for the care of breastfeeding mothers and infants and do not delineate an exclusive course of treatment or serve as standards of medical care. Variations in treatment may be appropriate according to the needs of an individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 82 publications
0
115
0
3
Order By: Relevance
“…Also, infants born to mothers with higher glucose concentrations have been shown to have a significant catch‐down weight in infancy . Some of these infants, but not all, may need to be supplemented with infant formula and hospital procedures on the management of these conditions may affect breastfeeding . The country‐specific differences in the influence of GDM on exclusive breastfeeding between Sweden and Finland in the TEDDY study were not explained, but it was hypothesised that different neonatal feeding guidelines and practices could be the cause .…”
Section: Discussionmentioning
confidence: 99%
“…Also, infants born to mothers with higher glucose concentrations have been shown to have a significant catch‐down weight in infancy . Some of these infants, but not all, may need to be supplemented with infant formula and hospital procedures on the management of these conditions may affect breastfeeding . The country‐specific differences in the influence of GDM on exclusive breastfeeding between Sweden and Finland in the TEDDY study were not explained, but it was hypothesised that different neonatal feeding guidelines and practices could be the cause .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants self-reported breastfeeding data in this study and therefore it may be subject to recall bias. However, other studies have shown that maternal reports of breastfeeding duration are accurate for many years after women have stopped breastfeeding [34].…”
Section: Discussionmentioning
confidence: 97%
“…In this sample however, even among participants who achieved their planned duration of breastfeeding, only 36% exclusively breastfed while in the hospital. Unfortunately, in-hospital formula supplementation of healthy breastfeeding infants is all too common [30][31][32] and rarely medically indicated [33,34].…”
Section: Discussionmentioning
confidence: 99%